Persepsi Guru terhadap Pendekatan Deep Learning dalam Pembelajaran Sentra Bahan Alam di TKIT Al-Hasan Gowa: Teachers Perceptions of the Deep Learning Approach in Learning Natural Materials Center at TKIT Al-Hasan Gowa - Hafisah; St. Marwana Aisyah; Nurul Putri Ramadhani; Herman; Muharram (Universitas Ngudi Waluyo, 2026)
The deep learning approach emerges as a strategic solution aimed at fostering comprehensive conceptual understanding through real life experiences, reflective activities, and active engagement in learning within the natural material learning center. This study employed a descriptive qualitative method with a phenomenological research design. Data were collected through observations, interviews, and documentation of learning activities in the natural-material center using the deep learning approach. The research subjects consisted of three teachers at TKIT Al-Hasan Gowa who implemented deep learning in the natural-material learning center. The data were analyzed using the Miles & Huberman model, which includes data collection, data reduction, data display, and conclusion drawing or verification. The results of the study indicate that teachers have a positive perception of the application of the deep learning approach in natural materials-based learning. The implementation of this approach encourages children to think critically, understand concepts comprehensively, and learn from direct experiences. Implementing deep learning in nature-based learning centers provides children with ample opportunities to experiment directly with various materials such as leaves, water, and rocks. However, the implementation still faces various challenges, including limited learning time and a lack of supporting resources. Therefore, support from schools and the government is needed to provide learning facilities and training for teachers so that the deep learning approach can be effectively optimized at TKIT Al-Hasan Gowa. ABSTRAK Pendekatan deep learning hadir sebagai solusi strategis yang bertujuan untuk mendorong pemahaman konsep secara komprehensif melalui pengalaman nyata, reflektif dan keterlibatan aktif dalam proses pembelajaran sentra bahan alam. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian fenomenologi. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi kegiatan pembelajaran sentra bahan alam dengan pendekatan deep learning. Subjek penelitian diperoleh dari tiga guru TKIT Al-Hasan Gowa yang menerapkan pembelajaran sentra bahan alam melalui pendekatan deep learning dan data di analisis menggunakan Miles & Huberman dari pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan ataupun verifikasi. Hasil penelitian menunjukkan bahwa guru memiliki persepsi positif terhadap penerapan pendekatan deep learning dalam pembelajaran sentra bahan alam. Implementasi pendekatan ini mampu mendorong anak berpikir kritis, memahami konsep secara menyeluruh, serta belajar dari pengalaman langsung. Melalui pelaksanaan deep learning dalam kegiatan sentra bahan alam memberikan kesempatan luas bagi anak untuk bereksperimen secara langsung dengan berbagai material seperti daun, air, dan batu. Namun, pelaksanaannya masih menemukan beragam kendala berupa keterbatasan waktu pembelajaran dan minimnya sarana pendukung. Oleh karena itu, dukungan pihak sekolah maupun pemerintah diharapkan mampu menyediakan fasilitas pembelajaran dan pelatihan bagi guru agar optimalisasi penerapan pendekatan deep learning di TKIT Al-Hasan Gowa berlangsung secara efektif.